Symmetric and folded Tori connected Torus Network - Rahman, M.M. Hafizur; Inoguchi, Yasushi; Faisal, Faiz Al; Kundu, Monoz Kumar (Academy Publisher, 2011)
Hierarchical interconnection networks provide high performance at low cost by exploring the locality that exists in the communication patterns of massively parallel computers. A Symmetric Tori connected Torus Network (STTN) is a 2D-torus network of multiple basic modules, in which the basic modules are 2D-torus networks that are hierarchically interconnected for higher-level networks. We also fold the STTN to minimize the length of the longest wire of STTN. The folded network is called Folded Tori connected Torus Network (FTTN). In this paper, we present the architecture of the STTN and FTTN, addressing of node, routing of message, and evaluate the static network performance of STTN, FTTN, TTN, TESH, mesh, and torus networks. It is shown that both the STTN and FTTN possess several attractive features, including constant node degree, small diameter, low cost, small average distance, moderate bisection width, and high fault tolerant performance than that of other conventional and hierarchical interconnection networks. We further evaluate the longest wire length of FTTN and compare it with other networks. We found that the longest wire length of the FTTN is far lower than that of other networks considered in this paper while keeping good static network performance. It is just about (1/2mth) of its rival STTN.